2002
DOI: 10.1021/es010609f
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Nonuniformly Distributed Immiscible Liquid:  Intermediate-Scale Experiments and Mathematical Modeling

Abstract: The purpose of this work is to examine the effect of nonuniform distributions of immiscible organic liquid on dissolution behavior, with a specific focus on the condition dependency of dissolution (i.e., mass transfer) rate coefficients associated with applying mathematical models of differing complexities to measured data. Dissolution experiments were conducted using intermediate-scale flow cells packed with sand in which well-characterized zones of residual trichloroethene (TCE) and 1,2-dichloroethane (DCA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 28 publications
6
44
0
Order By: Relevance
“…Subsamples of the contaminated media were collected during packing and subjected to solvent extraction to ensure that the saturations were close to the target value (approximately 14% for all experiments except the Pool experiment). The results of prior studies have shown that this method of emplacement produces relatively uniform distributions of immiscible liquid within the source zone (e.g., Brusseau et al, 2000Brusseau et al, , 2002. For the "pool" experiment, the water table was raised above the top boundary after excavation, and the zone was packed with 724-μm diameter sand.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsamples of the contaminated media were collected during packing and subjected to solvent extraction to ensure that the saturations were close to the target value (approximately 14% for all experiments except the Pool experiment). The results of prior studies have shown that this method of emplacement produces relatively uniform distributions of immiscible liquid within the source zone (e.g., Brusseau et al, 2000Brusseau et al, , 2002. For the "pool" experiment, the water table was raised above the top boundary after excavation, and the zone was packed with 724-μm diameter sand.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of subsurface heterogeneity and non-uniform immiscibleliquid distribution on mass-removal behavior and associated aqueous-phase concentrations (mass flux) has been examined for some time through laboratory, modeling, and field studies (e.g., Schwille, 1988;Dorgarten, 1989;Guiguer, 1991;Anderson et al, 1992;Brusseau, 1992;Guarnaccia and Pinder, 1992;Mayer and Miller, 1996;Berglund, 1997;Nelson and Brusseau, 1997;Blue et al, 1998;Powers et al, 1998;Unger et al 1998;Broholm et al, 1999;Brusseau et al, 1999;Frind et al, 1999;Zhang and Brusseau, 1999;Brusseau et al, 2000;Nambi and Powers, 2000;Saba and Illangasekare, 2000;Zhu and Sykes, 2000;Rivett et al, 2001;Sale and McWhorter, 2001;Brusseau et al, 2002;Jayanti and Pope, 2004;Lemke et al, 2004;Parker and Park, 2004;Phelan et al, 2004;Soga et al, 2004;Falta et al, 2005;Jawitz et al, 2005;Rivett and Feenstra, 2005;Fure et al, 2006;Lemke and Abriola, 2006;Brusseau et al, 2007). An early effort to quantify the relationship between contaminant mass flux reduction and mass removal, and the resultant reduction in risk, was presented by Freeze and McWhorter (1997).…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental concept of contaminant mass flux, its relationship to mass-removal processes and source-zone properties, and its impact on risk has long been established (e.g., Fried et al, 1979;Pfannkuch, 1984). The impact of subsurface heterogeneity, immiscibleliquid distribution, and mass-transfer dynamics on mass-removal behavior and aqueous concentration profiles (mass flux) has been examined for some time through laboratory, modeling, and field studies (e.g., Schwille, 1988;Dorgarten, 1989;Guiguer, 1991;Anderson et al, 1992;Brusseau, 1992;Guarnaccia and Pinder, 1992;Mayer and Miller, 1996;Berglund, 1997;Nelson and Brusseau, 1997;Powers et al, 1998;Unger et al, 1998;Broholm et al, 1999;Brusseau et al, 1999a;Frind et al, 1999;Zhang and Brusseau, 1999;Nambi and Powers, 2000;Zhu and Sykes, 2000;Brusseau et al, 2000Brusseau et al, , 2002 ; Saba and Illangasekare, 2000;Sale and McWhorter, 2001;Rivett et al, 2001;Enfield et al, 2002;Rao et al, 2002;Rao and Jawitz, 2003;Jayanti and Pope, 2004;Lemke et al, 2004;Parker and Park, 2004;Phelan et al, 2004;Soga et al, 2004;Falta et al, 2005a, b ;Jawitz et al, 2005;Feenstra, 2005, Fure et al, 2006;Lemke and Abriola, 2006;Suchomel and Pennell, 2006;Brusseau et al, 2007…”
Section: Introductionmentioning
confidence: 99%
“…Although concentration-based goals (i.e., contaminant plume concentration) such as maximum contaminant level (MCL) criterion are typically used for evaluating remediation performance, mass flux-based approaches (i.e., mass flux reduction (MFR)) should also be considered when making such determinations. Numerous studies investigating the effects of subsurface heterogeneity and immiscible liquid distribution on resulting aqueous phase concentrations and mass removal have been conducted over the last decade (e.g., Schwille 1988;Brusseau 1992;Mayer and Miller 1996;Blue et al 1998;Powers et al 1998;Brusseau et al 1999Brusseau et al , 2000Brusseau et al , 2002Brusseau et al , 2007Brusseau et al , 2008Zhang and Brusseau 1999;Nambi and Powers 2000;Saba and Illangasekare 2000;Rivett et al 2001;Johnson et al 2003;Parker and Park 2004;Soga et al 2004;Falta et al 2005;Jawitz et al 2005;Fure et al 2006;Lemke and Abriola 2006). Previous research comparing the performance of various enhancedsolubilization agents have primarily focused upon describing elution behavior and mass removal effectiveness Tick et al 2003;McCray and Brusseau 1998, McCray et al 2000, Blanford et al 2001Childs et al 2006).…”
mentioning
confidence: 99%
“…Evaluating the enhanced-solubilization experiments based on consistent comparison is critical for predicting contaminant transport, conducting risk assessments, and implementing appropriate remediation strategies for sites contaminated by immiscible liquids. Further knowledge, combined from previous studies within more complex systems (e.g., Boving and Brusseau 2000;Brusseau et al 2002;Lemke et al 2004;Fure et al 2006;Basu et al 2008;Brusseau et al 2007Brusseau et al , 2008DiFilippo and Brusseau 2008;Marble et al 2008;Carroll and Brusseau 2009) and newly developed experiments, will allow for a better understanding of the processes that control mass flux behavior, elution behavior, and mass removal from remediation systems utilizing enhanced-solubilization flushing.…”
mentioning
confidence: 99%